OP26 Effect of COVID-19 on presentations of decompensated liver disease in Scotland. (20th September 2022) - Manship, Tom; Brennan, Paul; Campbell, Iona; Campbell, Stewart; Clouston, Thomas; Dillon, John; Dillon, John; Forrest, Ewan; Fraser, Andrew; Goh, Tee Lin; Johnston, Michael; Khan, Muhammad; et al.
Abstract : The COVID-19 pandemic has presented unique challenges. Beyond the direct COVID-related mortality in those with liver disease, we sought to determine the effect of lockdown on people with liver disease in Scotland. The effect of lockdown on those with alcohol-related disease is of interest; and whether there were associated implications for a change in alcohol intake and consequent presentations with decompensated disease. We performed a retrospective analysis of patients admitted to seven Scottish hospitals with a history of liver disease between 1 April and 30 April 2020 (n=111) and compared across the same time in 2017, 2018 and 2019 (n=348). We also repeated an intermediate assessment based on a single centre to examine for delayed effects between 1 April and 31 July 2020 (n=89) compared to the same time period in 2017–2019 (n=284). Information was collected on patient demographics, disease characteristics, length of stay and inpatient mortality. We found that results and outcomes for patients admitted in 2020 were similar to those in previous years in terms of morbidity, mortality, and length of stay. In the Scotland-wide cohort: admission UKELD (United Kingdom Model for End-Stage Liver Disease) (56 (52–60) vs 54 (50–60); p<0.01), inpatient mortality ((10.9% vs 8.6%); p=0.499) and length of stay (8 days (4–15) vs 7 days (4–13); p=0.140). In the single centre cohort: admission UKELD (57 (53–62) vs 57 (53–60); p=0.246), inpatient mortality ((13.7% vs 10.1%; p=0.373) and length of stay (7 days (4–14) vs 7 days (3.5–14); p=0.525)). In the Scotland wide cohort, patients admitted in 2020 had a significantly higher serum sodium at presentation (137 (132–140) vs 135 (130–138) p<0.01)This group also had lower rates of HCC (1.8% vs 7.2%; p=0.04) In the single centre cohort, patients admitted in 2020 had lower rates of hepatic encephalopathy (21.3% vs 35.9%; p=0.01) and were less likely to be admitted due to decompensation (70.8% vs 82.7%; p=0.01). This assessment of immediate and medium-term lockdown impacts on those with chronic liver disease suggested a minimal effect on the presentation of decompensated liver disease to secondary care in terms of patient outcomes.